Remission of diabetes mellitus after ovariohysterectomy in a guinea pig with ovarian cysts - Kreilmeier-Berger, Theresa; Guija-De-Arespacochaga, Abigail; Bilek, Andrea; Künzel, Frank (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2019)
A 3-year-old intact female guinea pig was presented with a history of polydipsia, polyphagia, and hyperactivity combined with non-pruritic hair loss. The physical examination revealed bilateral alopecia mainly including the flanks and the ventral abdomen. Bilateral rounded masses just caudal to the kidneys were detected on abdominal palpation. Abdominal ultrasound examination confirmed bilateral ovarian cysts and an enlarged uterus with cystic lesions. Blood biochemistry revealed highly increased glucose and fructosamine concentrations. The final diagnoses were diabetes mellitus, bilateral ovarian cysts, and pathologic changes of the uterus. The guinea pig underwent ovariohysterectomy. After surgery, diabetes mellitus and all of the existing clinical signs were fully resolved. A causal relationship between hormonally active ovarian cysts and diabetes mellitus that commonly present independently from each other in the guinea pig can be strongly assumed in the present case. In suspicious cases of gestagen-induced diabetes mellitus ovariohysterectomy could be considered a potential treatment option in guinea pigs.
Keywords: Insulin resistance; gestagen-induced; fructosamine; bilateral symmetrical alopecia; polydipsia